Bacillus subtilis Colonization of Arabidopsis thaliana Roots Induces Multiple Biosynthetic Clusters for Antibiotic Production - Maan, Harsh; Gilhar, Omri; Porat, Ziv; Kolodkin-Gal, Ilana (Frontiers in Cellular and Infection Microbiology, 2021)
Beneficial and probiotic bacteria play important role in conferring immunity of their hosts to a wide range of bacterial, viral, and fungal diseases. B. subtilis is a Gram-positive bacterium that protects the plant from various pathogens due to its capacity to produce an extensive repertoire of antibiotics. At the same time, the plant microbiome is a highly competitive niche, with multiple microbial species competing for space and resources, a competition that can be determined by the antagonistic potential of each microbiome member. Therefore, regulating antibiotic production in the rhizosphere is of great importance for the elimination of pathogens and establishing beneficial host-associated communities. In this work, we used Bacillus subtilis as a model to investigate the role of plant colonization in antibiotic production. Flow cytometry and Imaging Flow Cytometry (IFC) analysis supported the notion that Arabidopsis thaliana specifically induced the transcription of the biosynthetic clusters for the non-ribosomal peptides surfactin, bacilysin, plipastatin, and the polyketide bacillaene. IFC was more robust in quantifying the inducing effects of A. thaliana, considering the overall heterogeneity of the population. Our results highlight imaging flow cytometry as a useful tool to study the effect of association with a plant host on bacterial gene expression. Furthermore, the common regulation of multiple biosynthetic clusters for antibiotic production by the plant can be translated to improve the performance and competitiveness of beneficial members of the plant microbiome.